The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/eaa.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Bog Bodies in Context: Developing a Best Practice Approach

Abstract: Bog bodies are among the best-known archaeological finds worldwide. Much of the work on these often extremely well-preserved human remains has focused on forensics, whereas the environmental setting of the finds has been largely overlooked. This applies to both the ‘physical’ and ‘cultural’ landscape and constitutes a significant problem since the vast spatial and temporal scales over which the practice appeared demonstrate that contextual assessments are of the utmost importance for our explanatory frameworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our data are presented in regional groupings, listing information about the landscape context at the time of deposition where known, the date and nature of the depositions (fragmented remains, articulated or not) and associated finds. We draw inspiration from Chapman and colleagues’ (2020) framework for a scalar interpretation of bog bodies that proposes a best practice structure, where the micro-scale includes the precise context of the body and its deposition, the meso-scale widens to the wetland context and the macro-scale includes longer-term considerations and landscape archaeology. We consider the micro- and meso-scales as far as is known and where relevant to our analysis in the regional sections.…”
Section: The Materialsmentioning
confidence: 99%
“…Our data are presented in regional groupings, listing information about the landscape context at the time of deposition where known, the date and nature of the depositions (fragmented remains, articulated or not) and associated finds. We draw inspiration from Chapman and colleagues’ (2020) framework for a scalar interpretation of bog bodies that proposes a best practice structure, where the micro-scale includes the precise context of the body and its deposition, the meso-scale widens to the wetland context and the macro-scale includes longer-term considerations and landscape archaeology. We consider the micro- and meso-scales as far as is known and where relevant to our analysis in the regional sections.…”
Section: The Materialsmentioning
confidence: 99%
“…Archaeological recovery has in fact shown that many of these bog bodies were carefully and deliberately positioned. They were not individuals who became lost in peatlands but were intentional internments in what may have been considered liminal places (Chapman 2015;Chapman et al 2020). In lowland areas of Europe, bodies considered to be dangerous in some way were sometimes deposited far from settlements in remote places such as bogs and swamps (Barber 2010).…”
Section: Time Depth Of Peatlandsmentioning
confidence: 99%
“…Furthermore, insight in peatland palaeogeography is key to understand (pre‐)historic human habitation (Van Beek, 2015; Van Beek et al, 2015) and to contextualise exceptional archaeological finds from wetlands (e.g. Chapman et al, 2019; Van Beek et al, 2019). Given the limited understanding on the development of Dutch inland peatlands, we selected a part of the coversand landscape in the Netherlands (Figure 2) as case study region, focusing on the northern area (approximately 4,700 km 2 ).…”
Section: Introductionmentioning
confidence: 99%